Edukasi Masyarakat Mengenai Suplemen dan Vitamin untuk Tumbuh Kembang Remaja dan Covid-19 - Ilil Maidatuz Zulfa; Fitria Dewi Yunitasari (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Covid-19 pandemic has hit worldwide for three years. During the pandemic, a proper diet and optimum consumption of vitamins and suplements will help to maintain the immune system. However, there is still lack of public awareness in fulfillness the nutrition need during pandemic. Hence, it is essentials to increase public knowledge and awareness through the through the provision of information in order to make people easier in choosing the best diet, vitamins and suplement to combat the pandemic.